L’activité des formateurs dans le cadre de la reconnaissance et la validation des acquis : l’évolution d’un instrument à partir de l’activité - Joana Fernandes; Marta Santos (Perspectives Interdisciplinaires sur le Travail et la Santé)
This research aimed to increase knowledge of the activity of trainers in a specific type of training, namely the recognition and validation of prior learning. The framework of key competencies emerged as the main tool in the trainers’ activity and, further more, mediated their interaction with the object, which was the recognition and validation of knowledge previously acquired by the trainees. Work activity analysis and group interviews with the trainers were used to better understand the nature of the tools underlying the activity as well as their ongoing updating process. The data analyses revealed that the tools evolved along with the activity, meaning that they were continuously redesigned through a process of tool genesis. It was also observed that the considerable leeway that these trainers had to contribute to the tools’ evolution was a source of satisfaction, as each trainer was allowed room to invent but was, at the same time, a source of discomfort due to the lack of validation of the tool evolution by the work group.